Pathophysiologie, Diagnose und Therapie des Zenker-Divertikels - Hussain, Timon; Maurer, Joachim T. (HNO, 2017)
Zenker’s diverticulum occurs at the dorsal pharyngoesophageal junction through Killian’s dehiscence and is caused by increased intrabolus pressure. Symptomatic disease most frequently affects male elderly patients. Primary symptom is oropharyngeal dysphagia, as well as regurgitation of undigested food, halitosis, and chronic aspiration. A barium swallow study is performed to confirm diagnosis. Treatment options for symptomatic patients include open surgery, as well as transoral rigid or flexible endoscopic procedures. Transoral procedures have become the main treatment approach over the past year thanks to reduced intraoperative complication rates compared to open surgery. The septum dividing the diverticulum from the esophagus is most commonly divided by a stapler device, papillotome, or laser. For high-risk patients who are poor candidates for general anesthesia, the procedure can be performed via flexible endoscopy in awake patients, albeit at an increased risk of recurrence.